Proteases of the complement system. (1st February 2004) - Sim, R.B.; Tsiftsoglou, S.A.
Abstract : The complement system is a group of about 35 soluble and cell-surface proteins which interact to recognize, opsonize and clear or kill invading micro-organisms or altered host cells (e.g. apoptotic or necrotic cells). Complement is a major part of the innate immune system. Recognition proteins such as C1q, MBL (mannan-binding lectin) and ficolins bind to targets via charge or sugar arrays. Binding causes activation of a series of serine protease proenzymes, such as C1r, C1s and MASP2 (MBL-associated serine protease 2), which in turn activate the atypical serine proteases factor B and C2, which then activate the major opsonin of the system, C3. Activated C3 binds covalently to targets, and is recognized by receptors on phagocytic cells. Two of the complement proteases, factors D and I, circulate not as proenzymes, but in activated form, and they have no natural inhibitors; their substrates are transient protein complexes (e.g. C3bB and C3bH) which form during complement activation. Factor B and C2 also have no natural inhibitor; they are active only when proteolytically cleaved and bound in an unstable, short-lived complex with C3b or C4b. C1r, C1s and the MASPs, in contrast, are regulated more conventionally by the natural serpin, C1-inhibitor. Complement proteases in general have very narrow specificity, and low substrate turnover with both natural and synthetic substrates. Excessive activation of complement is inflammatory, and causes tissue damage (e.g. in rheumatoid arthritis, or in ischaemia/reperfusion injury). Substances that regulate complement activation are likely to be useful in the regulation of inflammation. Complement activation might potentially be controlled at many different steps. Much attention has been focused on controlling the formation or activity of the protease complexes C3bBb and C4b2a (containing activated factor B and C2 respectively), as these generate the inflammatory peptides C3a and C5a.